ভাষার রাজপথ _ শোক হতে শক্তি : Center for Language Shoheed Minar Area, Dhaka University, Dhaka - Anika, Tahseen Reza (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2017.